1992
DOI: 10.1105/tpc.4.8.889
|View full text |Cite
|
Sign up to set email alerts
|

Mutations at the Arabidopsis CHM locus promote rearrangements of the mitochondrial genome.

Abstract: Nuclear recessive mutations at the chloroplast mutator (CHM) locus of Arabidopsis produce a variegated phenotype that is inherited in a non-Mendelian fashion. Molecular analysis of the cytoplasmic genomes of variegated plants from two independent chm mutant tines, using specific chloroplast and mitochondrial probes, showed that the chm mutations reproducibly induce the appearance of specific new restriction fragments in the mitochondrial genome. The presence of these restriction fragments cosegregated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 37 publications
4
98
0
1
Order By: Relevance
“…We have previously reported that NCS2 pale green leaf sectors have functionally and structurally altered chloroplasts, although the primary defect is in the mitochondrial DNA (Roussell et al, 1991). A mitochondrial DNA rearrangement also appears to be correlated with the maternally inherited variegation of plants carrying the chm ("chloroplast mutator") gene in Arabidopsis (Martínez-Zapater et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that NCS2 pale green leaf sectors have functionally and structurally altered chloroplasts, although the primary defect is in the mitochondrial DNA (Roussell et al, 1991). A mitochondrial DNA rearrangement also appears to be correlated with the maternally inherited variegation of plants carrying the chm ("chloroplast mutator") gene in Arabidopsis (Martínez-Zapater et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…A clue to the possible mode of action of Fr comes from the study of mutations in the Arabidopsis chloroplast mutator (CHM) locus, which result in the loss of mtDNA regions, producing green-white variegated leaves (Martinez-Zapater et al, 1992). Cloning of CHM revealed that it encodes a gene homologous with Escherichia coli MutS, which is involved in mismatch repair and DNA recombination (Abdelnoor et al, 2003).…”
Section: Fertility Restoration Through Mtdna Alterationmentioning
confidence: 99%
“…The various causes of this variegation include plastid ribosome deficiency (Han et al 1992, Hess et al 1993, alteration of plastid genome (Stoike and Sears 1998), mitochondrial dysfunction (Martínez-Zapater et al 1992, Sakamoto et al 1996, and deficiencies in carotenoid biosynthesis (Wetzel et al 1994). Variegated plants have played prominent roles in research on genetics (e.g., discovery of non-Mendelian inheritance) and morphology (e.g., analysis of cell lineage in leaf development).…”
Section: Introductionmentioning
confidence: 99%